The Battle of Bataan a complete history - Young, Donald J. 1930- (McFarland, 2009)
"This book begins with an overview of the Philippine, American, and Japanese forces which fought on Bataan, followed by chapters looking at the military buildup, the counterattack in the II Corps and the withdrawal from Abucay, the Japanese invasion, the Battle for the Points, the Battle of the Pockets, and, finally, the surrender and the death march"--Provided by publisher.